SEJARAH FIQH ABU HANIFAH - Nufiar Nufiar (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2013)
This paper attempts to discuss the figure of Abu Hanifa as an Islamicjurist, not as the others. One of the difficulties disclosures figure Abu Hanifa islocated on the lack of referral sources. I received only two papers that investigatedthe Abu Zahrah thoughts. Even then examine universally thought Abu Hanifah.Another source is the writings on biography and little thought of Abu HanifahIndonesian writers. Even then, according to the author quoted from the writings ofmany Abu Zahrah.